TRANSFORMASI PERILAKU ORGANISASI PESANTREN DALAM MENGHADAPI ANCAMAN EKSTRIMISME DIGITAL - Agus Hidayatullah; Zakariya Syafei; Rijal Firdaus; Eka Sri Mulyani (Cakrawala Pedagogik, 2026)
This study aims to analyze the transformation of pesantren organizational behavior in countering the threat of digital extremism through content management strategies and santri literacy development. Using a qualitative case study approach, this research examines various pesantren practices in managing digital narratives and strengthening santri resilience against extremist ideologies propagated through social media platforms. Data were collected through literature review, document analysis, and observation of pesantren digital literacy programs. The findings reveal that pesantren transformation occurs through three strategic pillars: first, the production of moderate counter-narratives by santri as digital content creators utilizing platforms such as YouTube, Instagram, and TikTok ; second, the integration of digital literacy into the traditional kitab kuning curriculum to reframe the meaning of jihad and da'wah narratives often exploited by radical groups ; and third, the exemplary leadership of kyai as moral anchors guiding santri in critically filtering extremist content . The study also identifies challenges including limited digital infrastructure, resistance to pedagogical change, and the gap between santri digital aspirations and pesantren institutional policies . These findings highlight the urgency of adaptive moderation—a framework that synthesizes pesantren traditions with digital transformation to safeguard santri ideological resilience while preserving Islamic moral integrity in the post-truth era .